Komunikasi Partisipatif pada Kegiatan Optimalisasi Pemanfaatan Lahan Pekarangan di Kecamatan Kajoran Kabupaten Magelang - Febri Palupi Muslikhah; Sarwititi Sarwoprasodjo; Dwi Sadono (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The success of the agricultural development program cannot be separated from the active participation of farmers which is manifested in the form of a response. The responses are delivered in the form of ideas, criticisms, dialogues and reflection actions. The Women Farmers Group (KWT) which is the main actor in the optimization program for the use of yard land is a determinant of the success of food security at the family level. The assistant extension workers are the hope of the government as a development facilitator who is able to facilitate and educate KWTs so that they are able to respond to the development programs being carried out. This article aims to describe the characteristics of the group, the role of the facilitator, KWT participatory communication and to analyze the relationship between the characteristics of the group and the role of the facilitator with participatory communication. This research is designed as a descriptive correlational survey research. The selection of respondents was taken by census as many as 12 KWT. The data that has been collected is then analyzed using the Spearman rank correlation test. The results obtained from the correlation test are that there is a very significant positive relationship between group characteristics, the role of the facilitator and KWT participatory communication. Keywords: participatory communication, women farmer groups, yard use